2019
DOI: 10.3390/cells8040348
|View full text |Cite
|
Sign up to set email alerts
|

Trehalose Modulates Autophagy Process to Counteract Gliadin Cytotoxicity in an In Vitro Celiac Disease Model

Abstract: Celiac disease (CD) is a chronic systemic autoimmune disorder that is triggered by the ingestion of gliadin peptides, the alcohol-soluble fraction of wheat gluten. These peptides, which play a key role in the immune response that underlies CD, spontaneously form aggregates and exert a direct toxic action on cells due to the increase in the reactive oxygen species (ROS) levels. Furthermore, peptic-tryptic digested gliadin peptides (PT-gliadin) lead to an impairment in the autophagy pathway in an in vitro model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 49 publications
(68 reference statements)
0
11
0
Order By: Relevance
“…Whole protein extraction and immunoblotting analysis was performed as previously described [26]. In detail, T98G cell pellets were resuspended in ice-cold RIPA buffer (150 mM NaCl, 50 mM Tris-HCl pH 8.0, 1 mM Triton X100, all from Sigma-Aldrich), supplemented with Complete Mini protease inhibitor cocktail (Roche, Basel, Switzerland).…”
Section: Immunoblotting Analysismentioning
confidence: 99%
“…Whole protein extraction and immunoblotting analysis was performed as previously described [26]. In detail, T98G cell pellets were resuspended in ice-cold RIPA buffer (150 mM NaCl, 50 mM Tris-HCl pH 8.0, 1 mM Triton X100, all from Sigma-Aldrich), supplemented with Complete Mini protease inhibitor cocktail (Roche, Basel, Switzerland).…”
Section: Immunoblotting Analysismentioning
confidence: 99%
“…Trehalose is a natural disaccharide, which is usually used as a medical desiccant. Nowadays, it has attracted much attention as a mTOR-independent autophagy inducer [ 12 , 174 ]. DeBosch et al [ 175 ] observed that Trehalose prevented cells from taking up glucose via blocking glucose transporters in the plasma membrane.…”
Section: Liver Steatosismentioning
confidence: 99%
“…The viability and apoptotic rates of glioma cells were quantified using the Muse Count & Viability or Annexin V and Dead Cell assays (Luminex, Austin, TX, USA), as described [40]. After trypsinization and collection, cells were washed 3 times with D-PBS, resuspended in D-PBS + 1% FBS (v/v) and 1 volume each of Count & Viability or Annexin V reagents, and incubated for 5 or 20 min at room temperature in the dark, respectively.…”
Section: Viability and Apoptosis Cytofluorimetric Analysismentioning
confidence: 99%